Quantitative assessment of hydrological response to vegetation change in the upper reaches of Luanhe River with the modified Budyko framework - Gao, Huishan; Li, Qingsong; Xiong, Guangcheng; Li, Baolu; Zhang, Jincai; Meng, Qingxiang (Frontiers in Ecology and Evolution, 2023)
For assessing the influence of vegetation variation in upper reaches of Luanhe River (URLR) on streamflow, we first computed the equation between underlying surface parameter (ω) and the Normalized Difference Vegetation Index (NDVI). Then we introduced the vegetation information into the Budyko equation and established a modified Budyko equation. Finally, the impact of vegetation change on streamflow in URLR were estimated using the modified Budyko equation. Results showed that: (1) The NDVI in the URLR presented an increasing trend from 1982 to 2016, which is opposite to the runoff depth. The sudden change of NDVI occurred in 1998, and a simple linear model between ω and NDVI was obtained (p<0.01). (2) The contribution rate of precipitation, potential evapotranspiration, NDVI, and anthropogenic factor on streamflow change during the changing period (1999-2016) are 44.99%, 11.26%, 29.45%, and 17.30%, respectively. Although precipitation is still the main driver of runoff impact in the ULRB, with the increasing vegetation in the ULRB, vegetation has become the second driver of runoff impact. followed by human activities and potential evapotranspiration. The mechanism of the effect of vegetation change on the water cycle needs to be further investigated. The results of this study can provide a theoretical basis for water use and conservation in the URLR.